Exploring yogurt awareness and purchase behaviour among Indian consumers - Ramandeep Singh; Rajesh Sharma; Jagadish Aditya Dinakar (Indian Journal of Dairy Science, 2026)
India’s probiotic industry shows promising growth, understanding consumer dynamics becomes imperative for stakeholders. This study investigated yogurt consumption among Indian consumers unveils critical insights into awareness and purchasing pattern in this dynamic market. This comprehensive analysis, conducted with 409 respondents from pan India. Chi -square test revealed the association between various socio demographic variables and factors like yogurt awareness, sources of information, places of purchase, and reason and purpose to buy yogurt. Urban females display the highest yogurt awareness, reflecting a key market segment. The Indian yogurt market operates on a push marketing model with dominance of relatives/friends as the primary information source. Supermarkets and hypermarkets serve as primary yogurt purchase points in India. This research aims to fill important gaps in knowledge by providing practical insights. These insights can help make strategic decisions easier for those looking to enter India’s dynamic yogurt market and contribute to the ongoing growth of its dairy industry.